Effect of Solution Treatment on the Microstructure and Mechanical Properties of IN718 Alloy. Issue 9 (September 2017) - Jinhui, Du; Xudong, Lv; Qun, Deng; Ying, Luo
Abstract: IN718 alloy exhibits excellent mechanical properties at high-temperature and good workability, which has been widely used in aircraft engine turbine disks, compressor disks, and power turbine shafts (i.e. rotating components). The mechanical properties of IN718 alloy, especially its creep and fatigue properties are a key factor determining the safety and reliability of engines. In this study, the effects of solution treatment at temperature ranging from 900 °C to 1050 °C on the microstructure and mechanical properties (including the tensile strength at room temperature and 650 °C, the stress-rupture behavior at 650 °C and 700 MPa, and the low-cycle fatigue behavior at 450 °C) were investigated by optical microscopy (OM), scanning electron microscopy (SEM) and electron backscatter diffraction (EBSD). The results show that in specimens subjected to solution treatment at temperature from 900 °C to 990 °C, the mass fraction of the δ-phase decreases with increasing temperature, whereas the grain size remains the same. However, in specimens treated at temperature ranging from 990 °C to 1050 °C, the δ-phase is dissolved and the grain size increases from 15 μm to 100 μm. With proper adjustment of the microstructure of IN718 alloy, this material can satisfy the requirements for high-temperature, corrosion-resistance, and radiation-tolerance, such as the aviation, petrochemical, and nuclear power industries.